Social Media Usage of Non-Governmental Organizations: Red Cross Societies of the G7 Countries and the Turkish Red Crescent - Hayriye Görkemli (Erciyes University, 2021)
Nowadays, with the emergence of the internet concept and its continuous development, non-governmental organizations have started to use these channels to maintain their existence and to promote themselves. In this study, it is examined how non-governmental organizations in developed countries and Turkey use their Twitter accounts. The study covers a period of six months (from May 1 to October 31, 2019). The universe of this study consists of all Red Cross organizations in developed countries and the Turkish Red Crescent. The sample of the study consists of Germany, Italy, France, the USA, England, Japan, and Canada, which are G7 countries and hold the majority of global wealth. In the scope of the study, G7 countries and the Turkish Red Crescent will be compared. As a result of the review, it is reached that the Turkish Red Crescent ranks first in the number of posts on Twitter and uses visual icons like other Red Cross organizations in the study. Moreover, similar to other institutions, the Turkish Red Crescent does not go into time and day limitations in their posts. It can be said that all the NGOs under the study used this medium effectively; however, the biggest deficiency is that they are not successful in answering the comments for the posts.